Pengaruh Good Corporate Governance Dan Profitabilitas Terhadap Nilai Perusahaan Dengan Pengungkapan Kebijakan Dividen Sebagai Variabel Pemediasi (Studi Kasus Perusahaan Manufaktur Sektor Industri Aneka Tahun 2020-2022 Yang Terdaftar Di Bursa Efek Indonesi - Novi Syam Putri; Bambang Sudiyanto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The population of various industrial sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2020-2022, this study aims to analyze the impact of good corporate governance, or with indicators of the size of the board of directors and the board of commissioners, on profitability calculated using Return on Asset on firm value and dividend policy as an intervening variable. According to this study, dividend policy is positively and significantly influenced by the size of the board of commissioners, but profitability and board size have no real influence on dividend policy. Tobin's q is positively and significantly influenced by board size and profitability, while dividend policy and board size have an insignificant effect. However, dividend policy cannot mediate the effect of profitability and good corporate governance on Tobin's Q. Keywords: Good Corporate Governance, Profitability, Firm Value, Dividend Policy.